Miniature All-Silica Microbubble-Based Fiber Optic Fabry-Perot Pressure Sensor with Pressure Leading-In Tube. (3rd April 2019) - Zhang, Huixin; Liu, Jia; Li, Jiashun; Jia, Pinggang; Feng, Fei; Hong, Yingping; Shen, Sanmin; Liang, Ting; Xiong, Jijun
Abstract : A novel all-silica fiber optic Fabry-Perot (FP) pressure sensor with pressure leading-in tube based on microbubble structure is developed and experimentally demonstrated. The FP cavity is formed by fixing the end face of the single-mode fiber (SMF) parallel to the outer surface of the microbubble, in which the microbubble with a diameter of about 318 μ m is constructed at the end of silica hollow tube. When external pressure is transmitted on the inner surface of the microbubble by the pressure leading-in tube, the FP cavity length changes with the diameter of microbubble. Experimental results show that such a sensor has a linear sensitivity of approximately 4.84 nm/MPa at room temperature over the pressure range of 1.1 MPa; the sensor has a very low temperature coefficient of approximately 2 pm/°C from room temperature to 600°C. The sensor has advantages of extremely low temperature coefficient, compact structure, and small size, which has potential applications for measuring pressure in high-temperature environment.